Low midnight ebook - Vaughn, Carrie (Kitty Norville, 2014)
Cormac, the Kitty Norville series' most popular supporting character, stars in his first solo adventure. Carrie Vaughn's Low Midnight spins out of the series on the wave of popularity surrounding Kitty's most popular supporting character, Cormac Bennett, a two-minded assassin of the paranormal who specializes in killing lycanthropes. In his first solo adventure, Cormac, struggling with a foreign consciousness trapped inside him, investigates a century-old crime in a Colorado mining town which could be the key to translating a mysterious coded diary...a tome with secrets that could shatter Kitty's world and all who inhabit it. With a framing sequence that features Kitty Norville herself, Low Midnight not only pushes the Kitty saga forward, but also illuminates Cormac's past and lays the groundwork for Kitty's future. At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.